2018
DOI: 10.4103/ijo.ijo_1240_17
|View full text |Cite
|
Sign up to set email alerts
|

Spectacle prescription in children: Understanding practical approach of Indian ophthalmologists

Abstract: Purpose:The aim of this study is to survey the management approach, regarding spectacle prescription in children, among Indian ophthalmologists.Methods:A web-based, anonymous questionnaire (multiple choice questions dealing with practical aspects of pediatric refraction), was sent to available database of Indian ophthalmologists. The survey responses (depicted in %) were compared using the amount of pediatric clientele in one's practice (Group A: <25%, Group B: 25% or more). The responses were also analyzed in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…A survey of hospital‐based optometrists in the United Kingdom indicates that most would prescribe a partial correction, reduced from the full refractive error. 8 Similar surveys have been conducted amongst optometrists or ophthalmologists in the United States, 9 , 10 India, 11 Saudi Arabia 12 and amongst community and hospital optometrists in the United Kingdom. 13 However, the reasons for this practice are unclear, and there are currently no data on the prescribing practices of community‐based optometrists in the United Kingdom.…”
Section: Introductionmentioning
confidence: 92%
“…A survey of hospital‐based optometrists in the United Kingdom indicates that most would prescribe a partial correction, reduced from the full refractive error. 8 Similar surveys have been conducted amongst optometrists or ophthalmologists in the United States, 9 , 10 India, 11 Saudi Arabia 12 and amongst community and hospital optometrists in the United Kingdom. 13 However, the reasons for this practice are unclear, and there are currently no data on the prescribing practices of community‐based optometrists in the United Kingdom.…”
Section: Introductionmentioning
confidence: 92%
“…Approximately 42% of the participants in this survey reported being involved in selecting the lens materials and frames for spectacle production. In a similar survey of ophthalmologists practicing in India, Monga and Dave[ 14 ] reported that close to 67% of the participants were involved in the spectacle-making process (lens material and frame selection). Regarding the decision to monitor refraction [Q4 Table 1 ], most participants (89%) reported that they followed-up with their patients and considered visual acuity, alignment, and binocular vision state.…”
Section: Discussionmentioning
confidence: 99%
“…Permission to use the questionnaire was granted by Monga and Dave. [ 14 ] The questionnaire was divided into two parts: the first part captured demographic data, and the second part included ten multiple-choice questions about commonly encountered pediatric refraction cases (supplemental file). The thrust of the survey was on the decision-making approach regarding when and how much the practitioner would prescribe for children for a given refractive error.…”
Section: Ethodsmentioning
confidence: 99%
“…More recently, All India Ophthalmologic Society (AIOS) Guidelines were released at the AIOC, Coimbatore, based on the deliberations of the group of Pediatric Ophthalmologists and Strabismologists of our country [ Table 1 ]. [ 1 ] In this issue, Monga and Dave[ 2 ] have published the results of their online survey done to understand the perspective of Indian ophthalmologists toward spectacle prescription in children. They have found a wide disparity in the pattern of pediatric spectacle prescription among the responders.…”
mentioning
confidence: 99%